Body Language in the Tetun Language: A Morphosemantic and Anthropolinguistic Analysis - Assis Nunes, Gracia Firsti (Jurnal Indonesia Sosial Sains, 2026)
The use of body part terms in everyday expressions is a well-documented phenomenon across many languages, yet it remains underexplored in Tetun , one of the official languages of Timor-Leste. Body part lexemes in Tetun frequently appear as components in compound words, producing words that go far beyond their literal anatomical references. This research aims to describe the form-meaning relationship in body-part compound words in Tetun and to uncover the cultural values and social concepts reflected within them. A qualitative descriptive approach was employed. Data were collected through observation and note-taking of natural speech, supplemented by dictionary consultation and interviews. The corpus consists of Tetun compound words containing body-part elements, classified and analyzed using Bauer's typology of compounding and Lieber's morphosemantic framework, alongside conceptual metaphor and metonymy theory. The analysis identifies three main categories of body-part compounds: compositional, metonymic, and metaphorical. Compositional compounds retain transparent semantic links between their elements, while metonymic compounds use a body part to refer to related functions or states. Metaphorical compounds, the most dominant category, map physical bodily experience onto abstract psychological and social domains. From an anthropolinguistic perspective, the body functions as a cultural symbol system through which Tetun speakers evaluate behavior, express emotions, and understand social roles. This study contributes to Tetun morphology documentation and enriches Austronesian linguistic studies by demonstrating how language, cognition, and culture intersect through bodily experience. The findings also have practical value for Tetun lexicography and language education